The influences of family leisure patterns on perceptions of family functioning. - Zabriskie, Ramon B.; McCormick, Bryan P. (Family Relations, 2001)
A study was conducted to test a model of family leisure functioning by examining the relationship of balance and core family leisure patterns to family adaptability and cohesion. Findings indicated that both balance and core family leisure patterns were notably linked to family cohesion.